Particularities of Surgical Treatment for the Neuropathic Diabetic Foot - Florin BOBIRCA; Anca BOBIRCA; Cristina JAUCA; Anca FLORESCU; Anca MUSETESCU; Dan DUMITRESCU; Andra BIRLIGEA; Andreea SCHVENINGER; Traian PATRASCU (Modern Medicine)
Diabetic neuropathy is one of the chronic complications of diabetes and along with other complications causes a pathology called diabetic foot. The present study analyzed a group of 164 patients admitted to the surgery department of the Clinical Hospital “Doctor Ioan Cantacuzino” Bucharest, between September and December 2019. The results of the study highlight the potential for contamination of neuropathic lesions and the need for curative surgery, most conservative. The conclusion of the analysis emphasizes that the imbalance of the underlying disease changes, in a negative sense, the prognosis of any complication of it.